PENERAPAN MODEL PEMBELAJARAN COOPERATIF LEARNING UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS 2 SDN 14/I SUNGAI BAUNG - Maryati, Eva; Saputra, Riski; Sonia, Anggun; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research began with initial data collection through observations of grade 2 students of SDN 14/I Sungai Baung in the 2024-2025 school year. Then improvements were made using the Classroom Action Research (PTK) method consisting of two cycles. This research involves four stages in each cycle: planning, implementation, observation, and reflection. The goal was to increase student activeness in Pancasila Education subjects by applying the Cooperative Learning approach. The results showed that the percentage of student activeness in learning Pancasila Education increased from cycle I to cycle II, from 52.27% with a poor category in cycle I to 72.72% with a good category in cycle II. The research was stopped in cycle II because the performance indicators had been achieved. In conclusion, the application of the Cooperative Learning model is proven to be able to increase student learning activeness in Pancasila Education subjects. Keywords: cooperative learning model, pancasila education, student activeness